Art Is Fun, Art Is Serious Business, and Everything in between: Learning from Art Therapy Research and Practice with Children and Teens - Einat S. Metzl (MDPI AG, 2022)
This paper explores the current theoretical frames of working with children and adolescents, considers the socio-political and developmental considerations for art therapy practice within settings, and systems in which children are embedded. An illustration of the use of art materials, processes, and products for children and adolescents based on an art therapist's clinical experience in school settings, mental health hospital, adolescents' clinic, and private practice then follows.